Institutional Challenges in the Implementation of Electronic Certificates in Land Services - Gustiaji Gustiaji; I Gusti Ayu Ketut Rachmi Handayani; Rahayu Subekti (Jurnal Hukum dan Pembangunan Ekonomi, 2025)
The Indonesia land administration system is presently undergoing a digitalization process, a highly significant development towards having a more transparent and accountable administration. However, the use of digital land certificates has still been facing a number of legal and institutional problems, making them rather ineffective to use. The objective of this research is to investigate the institutional problems involved in the creation of digital land certificates within the Indonesia land administration system. Using a qualitiative methodology with a focus on empirical legal studies, the research combines legal framework analysis and data collection procedures carried out through personal interviews, observation, and documentation, all done within the ATR/BPN Office, located within the Boyolali Regency. Data analysis involved a three-stage process: data reduction, data presentation, and drawing a conclusion, according to qualitiative analysis principles. The research focuses on the relationship between legal frameworks such as Law Number 5 of 1960 regarding the Principle of Agrarian Law and Government Regulation of the Minister of ATR/BPN Number 3 of 2023, and digital land registration process within Indonesia's land administration system. The results showed a significant problem with the process of digitalization, including a lack of infrastructure, a discrepancy in the capacity among personnel, lack of cooperation, and lack of public trust. The findings showed that the successful digitalization process within Indonesia's land administration system can only be accomplished by making the process legal and institutionally ready for such a digitalization process to occur effectively within Indonesia's land administration system.